PENGARUH KEPEMIMPINAN, PENDIDIKAN DAN PELATIHAN, DAN PENGEMBANGAN KARIER TERHADAP KINERJA PEGAWAI DI BKKBN - Dwi Hartini; Ahmad Dirwan (Prodi Magister Manajemen Universitas Dirgantara Marsekal Suryadarma, 2023)
This research aims to obtain fact data, and valid and correct information, and can be trusted about the influence of Leadership, Education and Training, and Career Development on Employees Performance in the Main Secretariat of the National Population and Family Planning Board. This research is conducted by using quantitative research approach, by using survey method, including survey, consolidation, test instrument through validity and reliability test, and data collection and processing of research result. The sample of this study is the entire population is affordable, and has the same character, that is as many as 76 employees echelon IV for the sample of research, taken at random simple, qualified research. The measurements in this study were conducted by giving the value of each item in question of all variables, the size of the values given in each statement using